PENGARUH SALES GROWTH DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT BATAVIA PROSPERINDO TRANS TBK PERIODE 2018 - 2024 - Ari Apriyana; Muhammad Restu Wijaya (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the influence of Sales Growth and Debt to Equity Ratio (DER) on Return on Assets (ROA) at PT Batavia Prosperindo Trans Tbk during the period 2018 to 2024. Return on Assets is a key indicator used to measure a company's efficiency in utilizing its assets to generate net income, while Sales Growth reflects the company's revenue performance, and Debt to Equity Ratio indicates the company's financial structure and risk level. This research employs a quantitative method with descriptive and associative approaches. The data used are secondary data obtained from the audited financial statements of the company. Statistical analysis was performed using IBM SPSS 25, which included classical assumption tests, multiple linear regression analysis, coefficient of determination, partial t-test, and simultaneous F-test. The results of the partial test (t-test) show that Sales Growth has a positive and significant effect on Return on Assets with a t-statistic of 8.970 and a significance value of 0.001. Debt to Equity Ratio also has a positive and significant effect on Return on Assets with a t-statistic of 4.008 and a significance value of 0.016. Furthermore, the simultaneous test (F-test) demonstrates that Sales Growth and Debt to Equity Ratio together have a significant effect on Return on Assets with an F-statistic of 41.716 and a significance value of 0.002. The coefficient of determination (R Square) is 0.954, indicating that 95.4% of the variance in Return on Assets can be explained by Sales Growth and Debt to Equity Ratio, while the remaining 4.6% is influenced by other factors outside this research framework.